2022
DOI: 10.1097/adm.0000000000000981
|View full text |Cite
|
Sign up to set email alerts
|

Shifting Medication Treatment Practices in the COVID-19 Pandemic: A Statewide Survey of Pennsylvania Opioid Treatment Programs

Abstract: Objectives: We sought to understand how opioid treatment programs (OTPs) adapted OTP operations to the COVID-19 pandemic and new federal regulations around methadone and buprenorphine. Methods: In fall 2020, we conducted an online survey of all 103 OTPs licensed by the Pennsylvania Department of Drug and Alcohol Programs, including clinical directors. Survey domains included changes to methadone take-home and telehealth practices; overdose and diversion prevention tactics; perceptions regarding how such change… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 31 publications
2
28
0
Order By: Relevance
“…21 Similarly, 66% of OTP directors surveyed in Pennsylvania noted they extended take-home supplies following the new flexibilities . 22 In a survey of all 8 Connecticut OTPs, directors reported that the number of patients receiving one or no take-home doses decreased from 37.5% to 9.6% (Brothers, 2021). 23 Three surveys asked patients about increased take-homes: In a survey of 104 OTP patients in North Carolina, 91.6% said they received some take-homes following the pandemic flexibilities relative to 68.3% who had received take-homes prior to the pandemic (Figgatt, 2021).…”
Section: B Findings and Implications For Federal Regulatorsmentioning
confidence: 99%
See 4 more Smart Citations
“…21 Similarly, 66% of OTP directors surveyed in Pennsylvania noted they extended take-home supplies following the new flexibilities . 22 In a survey of all 8 Connecticut OTPs, directors reported that the number of patients receiving one or no take-home doses decreased from 37.5% to 9.6% (Brothers, 2021). 23 Three surveys asked patients about increased take-homes: In a survey of 104 OTP patients in North Carolina, 91.6% said they received some take-homes following the pandemic flexibilities relative to 68.3% who had received take-homes prior to the pandemic (Figgatt, 2021).…”
Section: B Findings and Implications For Federal Regulatorsmentioning
confidence: 99%
“…23 Similarly, over 90% of OTPs in Pennsylvania noted less than half of their patients received 14-day take-homes, and 95% noted less than a quarter of their patients received 28-day take-homes . 22 No studies identified differences in take-home trends by provider characteristics (Lavender 2022, Krawczyk 2022). 22,31 Findings suggest that even under a more permissive policy, providers will not necessarily permit all patients to receive maximum amounts of take-home supplies.…”
Section: B Findings and Implications For Federal Regulatorsmentioning
confidence: 99%
See 3 more Smart Citations